Effects of service quality, Umrah experience, place attachment, pilgrims memory and satisfaction on behavioural intentions of Umrah pilgrims - Sherbini, Ayman Ali H (2018)
The research in religious tourism that is focusing on understanding tourist behavioural intentions is still limited, especially the research related to Islamic tourism. Umrah, as one of the most important rituals in Islam, need further understanding in terms of the quality services provided and pilgrims experience. The main objective of this research is to examine the relationship between service evaluation variables; service quality and tourist satisfaction, place attachment, Umrah experience, tourist memory with the behavioural intention of Umrah pilgrims. Aiming to improve the tourism industry is applicable to the Saudi Arabia 2030 strategic vision seeking for alternative source of income for the country. To contribute to the marketing body of knowledge and support in the country vision, a model was developed to understand the pilgrims experience and its effect on their behavioural intentions in the future. Data were collected from 448 Malaysian Umrah performers. A quantitative methods approach was adopted from previous studies to measure each variable used in the research. Analysis of Moments Structure (AMOS) was implemented to analyse the relationships between the variables. The results of structural equation modelling revealed that Umrah experience has direct and indirect impact on behavioural intentions. Although direct effect of pilgrims satisfaction and behavioural intentions was not significant, the indirect effect through pilgrims memory was significant. In addition, Pilgrims memory mediates the relationship between Umrah Experience and behavioural intentions. Place attachment was examined in the study where it was found to be significant on Behavioural Intentions. Quality of services provided in Makkah was examined in the current research and its relationship with Pilgrims Satisfaction was statistically approved. Moreover, Umrah Experience has an effective role as moderator between Place Attachment and Behavioural Intentions. Theoretically, the study contributed to the body of knowledge by examining the Umrah experience effective domain, in one side, and analyse the antecedents of the pilgrims’ Behavioural intentions, on another side. Practically, the study provides management and marketing implications that enable Umrah service providers and Umrah authorities in Saudi Arabia to improve the industry.